The student's guide to optical microscopes - Brandt, William H., 1927- (Los Altos, CA. : Kaufmann, 1976)
A programmed text introducing the history, theory, and basic operating principles of an optical microscope.
Includes Microscopes, microscopy, and microbiology by Robert Barer originally published in v. 28 of the Annual Review of Microbiology.
Includes bibliographical references and index.
Keywords: Microscopes -- Programmed instruction; Microscopes -- Programmed instruction